EVALUATING THE RELATIONSHIP BETWEEN MORAL INTELLIGENCE AND SOCIAL CAPITAL AND STUDENTS' ENVIRONMENTAL BEHAVIORS - Sara Jamshidi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Background: Environmental behaviors are one of the issues and challenges of today's communities to protect the environment. Hence, the present study was conducted to evaluate the relationship between moral intelligence and social capital and environmental behaviors. Method: The research method is descriptive and the research design is correlational. The statistical population of the present study included all master and PhD students in human science fields of study in Islamic Azad University of Hamadan. In the present study, 336 students were selected as a statistical sample using stratified random sampling method appropriate to volume of each class. Three standard questionnaires, including moral intelligence questionnaire, social capital questionnaire and environmental behaviors questionnaire were used to collect research data. Research data were analyzed using LISREL and SPSS statistical software. Results: The research results revealed a positive and significant relationship between moral intelligence and social capital and environmental behaviors. Conclusion: It is concluded that university officials should pay attention to students' moral intelligence and social capital to improve environmental behaviors.